Ethical Values in The Myth of Marriage Prohibition in The Month of Suro - Hanif Fitri Yantari; Danur Putut Permadi (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2024)
This research aims to see how the myth of the prohibition of marriage in the month of Suro exists in Javanese society in Alun-alun Kidul, Pucangan, Kartasura, Sukoharjo. The method used in this research is descriptive analytic-qualitative with field research. This research was conducted in Alun-alun Kidul village, with the reason that this village is still included in the ring one area of the capital site of the Islamic Mataram kingdom, which is known as the heart of Islamic culture in Java. Interview and observation are the data collection techniques used in this research. The results of this study show that the myth of the prohibition of marriage in Suro month that is still believed by the community has values that can be applied in everyday life. Through Franz Magnis Suseno's Javanese ethics, it contains the theory of social harmony ethics and wisdom ethics.